Soils’ alteration in the the Izvorul Muntelui Lake watershed under the influence of the degradation processes - MONICA IOANA MUSCALU (Riscuri şi Catastrofe, 2019)
In the Izvorul Muntelui Lake watershed, soil degradation is due to agricultural activities, such as animal husbandry, specific to mountain areas, crops of corn, potato, fodder beet and vegetables, as well as the construction of communications roads, forestry and tourism activities. The relationship between human pressure and soil quality is inversely proportional to the fact that soils in the studied perimeter are also affected by unfavorable natural factors such as high relief, low temperatures, or constrictive skeleton. The deforestations in recent years emphasize the pluvial erosion and the geomorphological processes of the slope, whose intensification was observed in the basins of Bistrița, Bistricioara, Hangu, Schit, Grintieş, Bolăţău and Tifilic rivers. With a view to rendering in use degraded land and reducing soil erosion, measures are needed to limit agricultural production, reforestation, or improve soil quality in the coming years.